ANALYSIS OF THE ACCEPTANCE AND USE OF SI IDA APPLICATION BY THE COMMUNITY OF PURWOREJO DISTRICT BASED ON THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 3 - Farahatussonia, Dyna; Mulyani, Sri; Nugraha, Joko Tri; Kristianto, Yohanes Ivan Adi (Journal of Social Politics and Governance (JSPG), 2025)
Digital transformation in public services encourages the government to develop various technology-based innovations, one of which is through the SI IDA application developed by the DPMPTSP of Purworejo Regency, which aims to simplify and accelerate online licensing processes. However, in its implementation, there are still several obstacles experienced by the community so that some people still choose to take care of permits directly at the office. The purpose of this study is to examine the components that affect the acceptance and implementation of SI IDA among the inhabitants of Purworejo Regency, utilizing the UTAUT3 model. The employed research methodology is quantitative, utilizing survey techniques and data analysis with SEM-PLS using SmartPLS version 4.1.0.9. The findings of this investigation suggest that behavioral intention is substantially impacted by performance expectancy, social influence, hedonic motivation, and personal innovativeness.  In the interim, usage behavior is significantly influenced by personal innovativeness, facilitating conditions, and behavioral intention. On the other hand, effort expectancy, facilitating conditions, and habit sxert no substantial impact on behavioral in intention and habit has no influence on use behavior.